How to Safely Remove Live Nematode in The Eye - Irma Suwandi Sadikin; Husni Thamrin; Ersyad Hamda (Majalah Oftalmologi Indonesia, 2020)
Objective: To provide information about a safe and easy technique to remove live nematode in the anterior chamber. Case Presentation: A 21-year old male presented with a sudden-onset of pain in right eye for 5 days. The complaint was accompanied with irritation and photophobia. On examination, visual acuity was 6/6,5 with his best corrected, with circumcorneal congestion. We performed slit-lamp examination on the AC and witnessed a thin, white motile object with wriggling movement, that was swimming live in AC. The worm was removed surgically from AC by using forceps and adding lidocain with nacl 0,9% intracorneal to stop its movement. The worm was sent to pathological anatomy department to be examined microscopically. Conclusion: A method of using lidocaine as a chemoparalysis substance has been proven effective to facilitate an easy removal of the worm so as to prevent major harm to the ocular structure.